Good and bad sides of TGFβ-signaling in myocardial infarction - Euler, Gerhild (Frontiers in Physiology, 2015)
Myocardial infarction is a prevailing cause of death in industrial countries. In spite of the good opportunities we have nowadays in interventional cardiology to reopen the clotted coronary arteries for reperfusion of ischemic areas, post-infarct remodeling emerges and contributes to unfavorable structural conversion processes in the myocardium, finally resulting in heart failure. The growth factor TGFbeta is upregulated during these processes. In this review, an overview on the functional role of TGFbeta-signaling in the process of cardiac remodeling is given, as it can influence apoptosis, fibrosis and hypertrophy thereby predominantly aggravating ischemia/reperfusion injury.